Sol-gel derived (Ba,Sr)TiO$_3$ thin films for tunable devices - D. Czekaj; A. Lisińska-Czekaj; T. Orkisz; K. Osińska; L. Kozielski (Archives of Acoustics)
The present study is devoted to synthesis and investigation of basic properties of ferroelectric thin films. The sol-gel-type chemical solution deposition method was used for preparation of (Ba$_{0.6}$Sr$_{0.4}$)TiO$_{3}$ (BST) thin films. The thin films were characterized in terms of their microstructure, crystalline structure, chemical composition and dielectric properties. It was found that the BST thin films adopted cubic crystallographic symmetry of the space group $Pm3m$, whereas the chemical composition of the thin films corresponded well with the chemical composition of the solution. Complex impedance spectroscopy was used to measure frequency-dependent dielectric properties of the thin films. Due to the high tunability and low dielectric loss, great application potential of these ferroelectric thin films was considered especially as tunable dielectric devices.